2020
DOI: 10.1177/2333794x20982438
|View full text |Cite
|
Sign up to set email alerts
|

A Vague Gluteal Swelling in a Neonate: Challenges in Its Diagnosis and Management. Short Title-Sacroccoygeal Teratoma

Abstract: Sacro coccygeal teratoma (SCT) is the most common extra gonadal neoplasm in the pre sacral area occurring in neonatal period. They mostly occur in the midline with a female preponderance. They are usually attached to coccyx, They are believed to be arising from totipotent cells that originate from primitive knot (Hensen’s node), hence are usually attached to coccyx. Infection in a sacrococcygeal teratoma has been rarely reported. Here is a report of a case of vague gluteal mass in a neonate and challenges in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(B) Magnetic resonance image of the immature teratoma coccygeal teratomas are thought to be derived from totipotent cells of the Hensen's node (primitive knot), an area at the cranial end of the primitive streak. 6,7 Other authors reported rare sites for lateralized teratoma development, such as kidney, liver, and temporozygomatic region. 8,9 Rare lateralized extragonadal localizations should not mislead the clinical suspicion of teratomas, and a primary localization should always be excluded.…”
Section: Gluteus As a Rare Localization Of Extragonadal Teratomamentioning
confidence: 99%
“…(B) Magnetic resonance image of the immature teratoma coccygeal teratomas are thought to be derived from totipotent cells of the Hensen's node (primitive knot), an area at the cranial end of the primitive streak. 6,7 Other authors reported rare sites for lateralized teratoma development, such as kidney, liver, and temporozygomatic region. 8,9 Rare lateralized extragonadal localizations should not mislead the clinical suspicion of teratomas, and a primary localization should always be excluded.…”
Section: Gluteus As a Rare Localization Of Extragonadal Teratomamentioning
confidence: 99%
“…Teratomas develop along the midline because they originate from the incomplete differentiation of totipotent primordial cells that arise in the yolk sac and migrate along the mesentery to the gonadal ridge during the 4 th -5 th week of embryologic development 3,4 . Indeed, most of the gluteal teratomas reported in literature are lateralized sacrococcygeal teratomas with a connection to the coccyx, since sacrococcygeal teratomas are thought to be derived from totipotent cells of the Hensen's node (primitive knot), an area at the cranial end of the primitive streak 7,6 .…”
mentioning
confidence: 99%